1989
DOI: 10.1063/1.102239
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon microstructure as studied by transmission electron microscopy

Abstract: A transmission electron microscopy study of microstructural defects in proton implanted silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…A sponge like morphology of PS has been characterized in terms of fractals (an intricate infrastructure consisting of a hierarchy of pores within pores) within certain finite length scale [53]. Both, quantum confinement of electrons in the nanowire and the contribution of defect/disordered states present in this system are important to explain the origin of luminescence in PS [25].The presence of disordered/amorphous phase has been reported earlier from EPR measurements [54].…”
Section: Porous Siliconmentioning
confidence: 95%
“…A sponge like morphology of PS has been characterized in terms of fractals (an intricate infrastructure consisting of a hierarchy of pores within pores) within certain finite length scale [53]. Both, quantum confinement of electrons in the nanowire and the contribution of defect/disordered states present in this system are important to explain the origin of luminescence in PS [25].The presence of disordered/amorphous phase has been reported earlier from EPR measurements [54].…”
Section: Porous Siliconmentioning
confidence: 95%
“…Branched pores are generally smaller than the primary pores. 40,393,448,449 The degree of branching and interpore connection depends strongly on doping concentration. For heavily doped materials, pores are generally branched.…”
Section: Influence Of Anodization Parameters On Microstructure Of Psimentioning
confidence: 99%
“…Cross-section transmission electron miscroscopy of porous silicon (Chuang, Collins & Smith, 1989) has shown that large pores have a distribution between 400 and 2500 A, regardless of dopant type or anode condition. In a sample prepared with current density at 10 mA cm -2 and with HF concentration at 10%, pores of --~ 500 A separated by --~ 3200 A were observed.…”
Section: Applicability Of Og'q~ Scans For Structural Analysismentioning
confidence: 99%